Cp*Co III -catalyzed C-H activation of (Hetero)arenes : expanding the scope of base-metal-catalyzed C-H functionalizations - Yoshikai, Naohiko (2015)
Directed activation: Cationic Cp*CoIII (Cp*=1,2,3,4,5-pentamethylcyclopentadienyl) complexes, either well-defined or in situ-generated, promote catalytic functionalization of arene C[BOND]H bonds with a variety of electrophilic reaction partners by directed C[BOND]H activation. These complexes not only emulate known reaction patterns of Cp*RhIII analogues, but also exhibit remarkable catalytic activity or unique reactivity. DG=Directing group.